Congenital etiologies of exocrine pancreatic insufficiency - Scheers, Isabelle; Berardis, Silvia (Frontiers in Pediatrics, 2022)
Congenital exocrine pancreatic insufficiency is a rare condition. In a vast majority of patients, exocrine dysfunction occurs as part of a multisystemic disease, the most prevalent being cystic fibrosis and Shwachman-Bodian-Diamond syndrome. Recent fundamental studies have increased our understanding of the pathophysiology of these diseases. Exocrine pancreatic dysfunction should be considered in children with failure to thrive and fatty stools. Treatment is mainly supportive and consists of pancreatic enzyme replacement and liposoluble vitamins supplementation.